PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP WANITA USIA SUBUR TENTANG PEMERIKSAAN IVA TEST - Nisah, Chairun; Ratna Dewi, Eliana, (JURNAL MEDIA KESEHATAN, 2017)
IVA Test is a simple method in early detection of cervical cancer early. The target of IVA Test is WUS aged 15-49 years. In Bengkulu Province WUS who perform the examination of cervical cancer detection by IVA test method is still low. The purpose of this study is to determine the effect of health education on knowledge and attitude of WUS on examination of IVA test in the work area of Sukamerindu Puskesmas Bengkulu City 2017 ".This research use pre experiment method one group pretest - posttest design. Population taken in this research is married WUS aged 20-49 years in work area of Sukamerindu health center with sample amounted to 30 people taken by purposive sampling technique. Sampling is done by purposive sampling technique. Data analysis using T-dependent Test.The results of this study obtained the average knowledge before the provision of health education that is 6.80 and the average after 13.00 with mean difference 6.2.And obtained the average attitude before the provision of health education that is 35.50 and the average after 38.80 with mean difference 3,3. It was concluded that health education influenced WUS knowledge and attitude about IVA test in Sukamerindu Puskesmas area of Bengkulu city in 2017.It is expected that the puskesmas can actively conduct home visits to provide health education, especially in providing information about the examination of IVA test to married WUS to reduce the risk of cervical cancer.